"It's Hard Out Here if You're a Black Felon": A Critical Examination of Black Male Reentry. (September 2019) - Williams, Jason M.; Wilson, Sean K.; Bergeson, Carrie
Formerly incarcerated Black males face many barriers once they return to society after incarceration. Research has long established incarceration as a determinant of poor health and well-being. While research has shown that legally created barriers (e.g., employment, housing, and social services) are often a challenge post-incarceration, far less is known of Black male's daily experiences of reentry. Utilizing critical ethnography and semi-structured interviews with formerly incarcerated Black males in a Northeastern community, this study examines the challenges Black males experience post-incarceration.